Relationship between GLOBE organizational culture dimensions, job satisfaction and leader-member exchange in Serbian organizations - Jelena Vukonjanski; Milan Nikolic; Olga Hadézic; Edit Terek; Milena Nedeljkovic (Journal for East European Management Studies, 2012)
The aim of this paper is to investigate the relationships between GLOBE organizational culture dimensions, facets of job satisfaction and the leadermember exchange relation in Serbian organizations. One of the most important aspects of this study was the demonstration of the utility of applying more general cultural theory to the study of organizational cultures. The sample consists of 256 middle managers in Serbian organizations. The results obtained proved that organizational culture dimensions are significant predictors of all facets of job satisfaction and that relations between some organizational culture dimensions and facets of job satisfaction are moderated by the leader-member exchange (LMX) variable. Our results may be of interest for human resource managers in Serbian organizations as well as for foreign investors. – – Das Ziel dieses Artikels ist es, die Beziehungen zwischen den GLOBE Kultur- Dimensionen, der Arbeitszufriedenheit und dem Führer-Mitarbeiter-Verhältnis in serbischen Organisationen zu untersuchen. Einer der wichtigsten Aspekte dieser Studie war die Demonstration der Nützlichkeit der Anwendung allgemeiner Kulturtheorien bei der Untersuchung von Unternehmenskulturen. Die Stichprobe besteht aus 256 mittleren Führungskräften aus serbischen Organisationen. Die erzielten Ergebnisse zeigen, dass die Organisationskultur- Dimensionen signifikante Prädiktoren für alle Facetten der Arbeitszufriedenheit sind. Zudem werden die Beziehungen zwischen den Organisationskultur- Dimensionen und der Arbeitszufriedenheit durch die Führer-Mitarbeiter- Verhältnis-Variable moderiert. Unsere Ergebnisse können für Personalmanager in serbischen Organisationen von Interesse sein, ebenso wie für ausländische Investoren.
Keywords: 650; Organizational culture; job satisfaction; LMX; Serbia